TINDAK TUTUR EKSPRESIF GURU TERHADAP SISWA KELAS VII DALAM PEMBELAJARAN BAHASA INDONESIA SMP NEGERI 1 ENAM LINGKUNG PADANG PARIAMAN - Amelia, Rizkiqa; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT "Teacher's Expressive Speech Against Class VII Students in Indonesian Language Learning at SMP Negeri 1 Enam Lingkung, Padang Pariaman Regency". Essay. Indonesian Language and Literature Education Study Program. Indonesian Language and Literature Department and Regional Language and Art Faculty, Padang State University. The reason for this research was conducted at SMP Negeri 1 Enam Lingkung, Padang Pariaman Regency, grade VII, was the strategy of teacher's utterance on how students sometimes still use mixed code in their speech. The intended speech acts such as speech acts praise, blame, criticize, thank you, congratulate, and condolence. Data collection was carried out by the skillful free listening (SBLC) technique, recording, and recording. Data obtained from recordings are then transcribed into written language. Based on the data analysis conducted it can be concluded as follows. First, the results of this study indicate that Indonesian language teachers in class VII 1 of SMP Negeri 1 Enam Lingkung use four types of expressive speech acts, namely expressive speech acts praise, expressive blame speech acts, expressive speech acts criticize, and expressive speech acts to thank. Secondly, the strategy of speaking Indonesian language teachers in class VII of SMP Negeri 1 Enam Lingkung, Padang Pariaman District, there are four, namely to speak frankly without further ado, to be forthright with pleasant politeness, to be forthright with small talk of negative politeness, and strategy berututr vaguely. The most dominant spoken strategy used by Indonesian teachers in class VII is the strategy of speaking honestly without further ado.Â Kata Kunci: Strategi, tindak tutur ekspresifÂ